Internal Determinants Affecting the Timeliness of Financial Reporting in IDX - Rifqi Dwi Mahendra; Suryana; Yayat Supriyatna; Leni Yuliyanti ‬‬‬‬‬‬‬‬‬‬‬ (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Timeliness in financial reporting is crucial for investors and stakeholders in making informed decisions. However, variations in financial performance may impact reporting timeliness. This study examines the effect of profitability, leverage, and company size on the timeliness of financial reporting in companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A quantitative approach with verificative methods was employed, source of secondary data from annual financial reports. The results revealed that profitability has a positive effect on the timeliness of financial reporting, while leverage and company size have no significant effect. These results indicate that financially successful companies tend to submit reports more promptly, whereas leverage and size do not play a determining role in reporting timeliness. The results of this study reinforce notion that sound financial condition encourages corporate compliance with reporting deadlines. On the other hand, companies with high leverage or larger size do not always experience delays in reporting, indicating that other factors may be more influential.